(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article is devoted to the aspects of designing and organizing the internal space of the terminals of modern airport complexes. The article provides a brief analysis of the current state of the passenger terminals of the world’s leading airports. Examples of existing experience in the design and construction of air terminal complexes are considered, trends in their further development are identified. The features of the functional-planning, architectural-spatial organization of modern air terminals and the basic principles of the formation of the internal structure of these facilities are studied. Airport design is one of the most difficult tasks in the practice of architects, which requires non-standard solutions to achieve impressive results. The article discusses new trends in the design and development of architecture and design in this area of design, namely, the Aerotropolis airport. One of the main tasks in the design of passenger terminals is the organization of a competent and thoughtful system of visual communication with the help of which a person can clearly and easily orient himself in space. Examples of the most successful solutions in organizing a visual communications system in passenger terminals are given. The article reveals patterns and new trends in the organization of the internal space of air terminal complexes, the use of energy saving technologies and modern environmentally friendly materials. Examples of the most successful solutions in this area, included in the list of the best airports in the world according to the results of the World Airport Awards competition, are considered. Conclusions are drawn regarding the primary tasks in the design of such complex objects. Proposals for the development of the functional planning structure and organization of the internal space of air terminals have been determined. The analysis of this topic is of considerable interest, since life offers new non-standard solutions.